The colonial past in the postcolonial present Eddie Romero's cavalry command - Hawkins, Michael (Plaridel : A Philippine Journal of Communication, Media, and Society, 2006)
In late 1963, Calvary Command, a fictional filmic account of the U.S. Army's successful pacification of a Philippine village during the Philippine-American War, beamed across movie screens in the United States. Made through the interdependent efforts of an American film studio, a Filipino director and crew, and a cast of both American and Filipino performers, Calvary Command was one of many co-produced films made in this decade. This paper examines Calvary Command in relation to other contemporaneous accounts of the American colonial period, considering its distinct accounting of this history as a function of the production process itself and the subjectivities of its director, Eddie Romero.